Pengaruh Kompetensi Manajerial dan Motivasi Terhadap Kinerja Pegawai di Puskesmas Sambongpari Kota Tasikmalaya - Eti Rahmawati; Enas Enas; Aini Kusniawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The problems faced in this study include (1) How does managerial competence affect employee performance at the Sambongpari Health Center, Tasikmalaya City? (2) What is the effect of motivation on employee performance at the Sambongpari Health Center, Tasikmalaya City? (3) How does managerial competence and motivation affect employee performance at the Sambongpari Health Center, Tasikmalaya City?. This study aims to study, know, and analyze (1) The influence of managerial competence on employee performance at the Sambongpari Health Center, Tasikmalaya City. (2) The effect of motivation on employee performance at the Sambongpari Health Center, Tasikmalaya City. (3) The influence of managerial competence and motivation on employee performance at the Sambongpari Health Center, Tasikmalaya City. The method used in this study is explanatory survey, while the technical data analysis is validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) Managerial competence has a positive effect on employee performance at the Sambongpari Health Center, Tasikmalaya City. This means that if managerial competence is improved, the performance of employees at the Sambongpari Health Center in Tasikmalaya City will also increase. (2) Motivation has a positive effect on employee performance at the Sambongpari Health Center, Tasikmalaya City. This means that if motivation is increased, the performance of employees at the Sambongpari Health Center in Tasikmalaya City will also increase. (3) Managerial competence and motivation have a positive effect on employee performance at the Sambongpari Health Center, Tasikmalaya City. This means that if managerial competence and motivation are improved, the performance of employees at the Sambongpari Health Center in Tasikmalaya City will also increase.